Finite Element Investigation of a 3D Frame Tool for HDPE Plate Bending in 5 GT Fishing Vessel Construction - Samuel Febriary Khristyson; Mascha R. A. Damanhuri; Paundra A. W. Sae (Jakarta Global University, 2025)
The bending accuracy of High-Density Polyethylene (HDPE) plates is a critical factor in the construction of 5 GT fishing vessels, particularly in achieving the required hull curvature. This study presents a finite element investigation of a 3D frame tool designed to assist the HDPE plate bending and marking process. The research integrates numerical simulation using the Finite Element Method (FEM) with experimental tensile testing to evaluate the structural performance and material behaviour of the HDPE plates. Material properties were obtained through tensile testing in accordance with DIN EN ISO 6892-1 standards, and the resulting stress–strain data were used to define the material model in the FEM analysis. Two design configurations of the 3D frame were evaluated under equivalent loading conditions of 27 N. The results show that geometric configuration and structural complexity influence stress distribution and safety factor values, although the differences between the two designs are not significant. The maximum stress values obtained from simulation were compared with experimental tensile strength data, and validation using point-wise error analysis showed a deviation of less than 5%, indicating good agreement between numerical and experimental results. The analysis suggests that HDPE plates with a thickness of 10–12 mm can be effectively formed using round bar iron with a diameter of 8–10 mm, with 8 mm identified as the most practical and efficient size for common applications. Overall, the proposed 3D frame design meets the safety criteria and demonstrates reliable structural performance for HDPE plate bending in small-scale fishing vessel construction. Future work should incorporate thermo-mechanical coupling to account for temperature-dependent material behavior during welding and field operations.